A case report of reptile-associated nidovirus (serpentovirus) in a ball python (Python regius) in Taiwan - LI, Wen-Ta (J Vet Med Sci, 2020)
Reptile-associated nidoviruses (serpentoviruses) have been reported to cause proliferative interstitial pneumonia in pythons and other reptile species. A captive, younger than 2 years old, intact female ball python (Python regius) showed increased oral mucus, wheezing, and audible breathing with weight loss. Gross and microscopic examination revealed large amounts of mucus in the esophagus and proliferative interstitial pneumonia. Serpentovirus genes were detected from the lung tissues by polymerase chain reaction. The current serpentoviruses was phylogenetically grouped with the serpentovirus previously identified in the US. No case of serpentovirus infection has been reported in Asia. The present report provides information of complete genome sequence and global distribution of serpentovirus.